Low Usage of Internet Banking: A Study on Scope International Malaysia - Tay, Chiat Chien (2012)
According to the CEO of SCOPE International, only 7% of Standard Chartered customers in Malaysia use the internet banking facilities and it is rather low as compared to ASEAN countries in 2010. Therefore, the objective of this research is to identify and determine the factors that influence the low usage of internet banking in Malaysia. This study is to provide a solution to solve SCOPE’s problem. The proposed sample size is 200 of Standard Chartered Bank customers. 204 out of 220 questionnaires is valid Standard Chartered respondents. In this study, both primary and secondary data will use for data collection. Reliability analysis, factor analysis are being used to check the variables’ reliability and validity. Furthermore, multiple regression is to check the relationship between independent variables and dependent variable. At the end, perceived ease of use, perceived usefulness, e-security and actual internet experience have the positive relationship with intention to use internet banking. The R2 of independent variables and intention to use internet banking is 64.6%. Besides, the equation is I = 0.615 + 0.333 PEU + 0.303 PU + 0.149 ES + 0.131 AEI. The R2 of intention and usage of internet banking is 52.1% the equation is Y = 0.476 + 0.856 Intention.